Analisis Kinerja Pendapatan Pajak Daerah Pada Badan Pendapatan Daerah (BAPENDA) Kabupaten Ogan Komering Ulu Tahun 2013-2017 (Ekonomika, 2020)
The research objective was to determine the performance of revenue at the OKU Regency BAPENDA office analyzed from the 2013-2017 Budget Realization Report. The method used is descriptive quantitative by using analysis of variance and income growth. From the results of the analysis it was concluded that the income performance based on analysis of variance in 2013-2017, which is an average of 87.59% in BAPENDA OKU Regency, results of variance analysis showed results below 100%, which means that BAPENDA OKU District has not been able to realize its regional tax revenues has been budgeted. Income growth from the budget realization report from 2013-2017 which reached an average of 11.86% because income growth in BAPENDA OKU Regency can be said to be good, although there are several types of taxes that have not been realized for that BAPENDA OKU Regency must optimize the results- the results of his income. From the results of the budget realization report that the author did show that the OKU Regency BAPENDA is very effective in realizing its income.